2005
DOI: 10.1017/s1074070800027188
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Genetically Modified Oil, Cornflakes, and Salmon: Evidence from a U.S. Telephone Survey

Abstract: This paper reports results from a U.S. national telephone survey on genetically modified foods (vegetable oil, cornflakes, and salmon). The survey featured a contingent valuation in which respondents chose between the GM and non-GM alternatives with an option of indifference. The binomial and multinomial logit models yielded estimated willingness to pay (WTP) to avoid the GM alternatives. Respondents were willing to pay 20.9%, 14.8%, 28.4%, and 29.7% of the base prices to avoid GM vegetable oil, GM cornflakes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…However, because the initial bid, B I , was a fixed value equal to the average market price of non-GM-fed beef rather than a randomly assigned bid value conventionally used in a standard double-bounded design, the nonrandomness of B I might have made the fitting of a double-bounded CV model inappropriate. Kaneko and Chern (2005) designed a questionnaire similar to Li et al's (2004) with more options for a consumer to select his or her preferred goods. They first requested respondents to choose, at the market price of the non-GM food at the survey time, a preference from (1) non-GM, (2) GM alternative, (3) Indifferent, or (4) Neither.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, because the initial bid, B I , was a fixed value equal to the average market price of non-GM-fed beef rather than a randomly assigned bid value conventionally used in a standard double-bounded design, the nonrandomness of B I might have made the fitting of a double-bounded CV model inappropriate. Kaneko and Chern (2005) designed a questionnaire similar to Li et al's (2004) with more options for a consumer to select his or her preferred goods. They first requested respondents to choose, at the market price of the non-GM food at the survey time, a preference from (1) non-GM, (2) GM alternative, (3) Indifferent, or (4) Neither.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of the indifference option in the CV question by Kaneko and Chern (2005) was an interesting idea. The indifference option provides a consumer with an alternate choice so that he or she is not forced to give a dichotomous response when he or she truly has no preference between the two products.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, if a GM food contained genetically modified animal ingredients, consumer's awareness to it would increase. [4] In china, there is a big difference among the different findings. A computer-assisted telephone survey to Guangzhou, Shanghai and Beijing organized by Greenpeace showed that only 35% of respondents will or are likely to purchase the GM food.…”
mentioning
confidence: 99%